New Targets in Heart Failure Drug Therapy - Correale, Michele; Tricarico, Lucia; Fortunato, Martino; Mazzeo, Pietro; Nodari, Savina; Di Biase, Matteo; Brunetti, Natale Daniele (Frontiers in Cardiovascular Medicine, 2021)
Despite recent advances in chronic heart failure management (either pharmacological or non-pharmacological), the prognosis of heart failure (HF) patients remains poor. This poor prognosis emphasizes the need for developing novel pathways for testing new HF drugs, beyond neurohumoral and hemodynamic modulation approaches. The development of new drugs for HF therapy must thus necessarily focus on novel approaches such as the direct effect on cardiomyocytes, coronary microcirculation, and myocardial interstitium. This review summarizes principal evidence on new possible pharmacological targets for the treatment of HF patients, mainly focusing on microcirculation, cardiomyocyte, and anti-inflammatory therapy.